Prevalence of Calodium hepaticum (Syn. Capillaria hepatica) in house mice (Mus musculus) in the Azores archipelago - Resendes, Ana (2009)
Calodium hepaticum (Syn. Capillaria hepatica) is a zoonotic liver nematode of mammals distributed worldwide. Rodents are believed to be the main reservoirs of this nematode. In this paper, prevalence of the parasite was analyzed in liver histological sections from 51 house mice (Mus musculus) caught in human-inhabited houses, from two localities (Furnas and Rabo de Peixe) on São Miguel island from the Azores archipelago (Portugal). Mean prevalence of infection was 19.6%, with 33.3% prevalence in Furnas and 4.1% in Rabo de Peixe (P = 0.07). No significant differences were found between the prevalence of infection and the age, body weight and the sex of mice. Hepatic lesions found were either acute and/or chronic stage and consisted of moderate to severe multifocal pyogranulomatous hepatitis with encapsulated eggs with typical bipolar plugs and moderate to severe necrotizing hepatitis consistent with larva tracks. Periportal inflammatory infiltration, hepatocyte regeneration and bile duct hyperplasia were also noted. In most cases, hepatic lesions occupied more than 50% of the liver, but despite severe lesions, in some mice, no signs of hepatic failure were noticed. The high rate of infection found in the present study suggests that house mice are an important reservoir for this parasite in the Azores and could have a role in human transmission.